Disrupted Sleep and Circadian Rhythms in Schizophrenia and Their Interaction With Dopamine Signaling - Ashton, Anna; Jagannath, Aarti (Frontiers in Neuroscience, 2020)
Sleep and circadian rhythm disruption (SCRD) is a common feature of schizophrenia, and is associated with symptom severity and patient quality of life. It is commonly manifested as disturbances to the sleep/wake cycle, with sleep abnormalities occurring in up to 80% of patients, making it one of the most common symptoms of this disorder. Severe circadian misalignment has also been reported, including non-24 hour periods and phase advances and delays. In parallel, there are alterations to physiological circadian parameters such as body temperature and rhythmic hormone production. At the molecular level, alterations in the rhythmic expression of core clock genes indicate a dysfunctional circadian clock. Furthermore, genetic association studies have demonstrated that mutations in several clock genes are associated with a higher risk of schizophrenia. Collectively, the evidence strongly suggests that sleep and circadian disruption is not only a symptom of schizophrenia but plays an important causal role in this disorder. The alterations in dopamine signaling that occur in schizophrenia are likely to be central to this role. Dopamine is well-documented to be involved in the regulation of the sleep/wake cycle, in which it acts to promote wakefulness, such that elevated dopamine levels can disturb sleep. There is also evidence for the influence of dopamine on the circadian clock, such as through entrainment of the master clock in the suprachiasmatic nuclei (SCN), and dopamine signaling itself is under circadian control. Therefore dopamine is closely linked with sleep and the circadian system; it appears that they have a complex, bidirectional relationship in the pathogenesis of schizophrenia, such that disturbances to one exacerbate abnormalities in the other. This review will provide an overview of the evidence for a role of SCRD in schizophrenia, and examine the interplay of this with altered dopamine signaling. We will assess the evidence to suggest common underlying mechanisms in the regulation of sleep/circadian rhythms and the pathophysiology of schizophrenia. Improvements in sleep are associated with improvements in symptoms, along with quality of life measures such as cognitive ability and employability. Therefore the circadian system holds valuable potential as a new therapeutic target for this disorder.